From the high school occupation movement in São Paulo (2015-2016) to the youth protagonism: neoliberalism, war-management and politic work - André Carreiro Kohan (Geografares, 2022)
This article seeks to analyze the secondary students’ movement, from the outbreak of the first wave of occupations in 2015 - especially the strategies and elaborations created by the movement against those of the State in its articulation with other social actors - until its end, after the second wave of the movement in 2016, when it was reabsorbed in and by the discourse of youth protagonism. This analysis started with the understanding of the secondary students’ movement as political work and with the recognition of the knowledge produced in it, which allowed us to trace the way in which the changes underway in the function of the public school correlated to a structural change of management-business, in a discourse shared among NGOs, academics, the state and international bodies since the late 1990s in Latin American countries. However, the consolidation of this project was only possible through an everyday tactic and strategy of warfare that goes back to a much earlier experience in social reproduction (and its forms of negation), as the secondary students understood it.